The role of immunoprophylaxis in prevention of vertical transmission of hepatitis B infection in cases who were admitted to Firat Medical Center - Dogan, Yasar; Aygun, A. Denizmen; Akarsu, Saadet; Yilmaz, Erdal; Kabakus, Nimet (Turkish Pediatrics Assoc, 2007)
Aim: This study aims to reveal the efficiency of immunoprophylaxis and Hepatitis B vaccine administration program applied on babies born from mothers with positive Hepatitis B surface antigen (HBsAg). Material and Method: Cases born from mothers with positive Hepatitis B surface antigen were included in the study. After blood samples were taken from the navel cord or a surface vein soon after birth for hepatitis indicators, recombinant hepatitis B Immunoglobin (HBIG) and recombinant hepatitis B vaccine were administered intramuscularly to all cases during the first 12 hours. 3 additional doses of Hepatitis B vaccine were administered on the 1st, 2nd and 12th months. Blood samples were taken 1 month after each administration, and the antiHBs titer levels were examined for 4 times. Results: 50 cases born from HBsAg positive mothers were included in the study. 33 (66%) percent of the caseswere females and 17 (34%) were males. Protective levels of anti HBs appeaed in 80% of cases after the first administration, (87.8% in females and 52.9% in males). While 98% prevention was ensured in anti-HBs levels of babies examined after one month following their second vaccination dose, antiHBs was negative in only one boy even after the second dose of vaccine. After the third dose, positive anti-HBs has been detected in protective levels in all patients. While the lowest antibody titer after the fourth dose was 38 mIU/ml, the highest titer was 1257 mIU/ml. Differences in mean anti-HBs titers of babies between the first and the second, the second and the third, the third and the fourth doses were founded statistically significant (p<0.000). Mean anti-HBs titers after the fourth administrations were higher ingirls compared to boys, however this difference was not statistically significant (p>0.05). Conclusions: All pregnant women must be tested routinely for HBsAg. Immunoprophylaxis and vaccination of the newborns born to mothers who are HBsAg (+) in the early postpartum period significantly prevent vertical transmission of Hepatitis B virus infection, independent from the serology of hepatitis B in newborns.
Firat Tip Merkezine getirilen olgularda hepatit B enfeksiyonunun dikey geçişinin önlenmesinde immünoprofilaksinin rolü
Keywords: Hepatitis B; immunoprophylaxis; newborn; perinatal transmission; vaccine